Measurement of the production cross section for single top quarks in association with W bosons in proton-proton collisions at s√=13s=13 TeV; Journal of High Energy Physics; Vol. 2018, iss. 10 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich (2018, 2018)
Title screen